Distance Metrics for Machine Learning and it's Relation with Other Distances - Yadav, Dipendra Prasad; Kumar, Nand Kishor; Sahani, Suresh Kumar (Mikailalsys Journal of Mathematics and Statistics, 2023)
In machine learning, distance metrics play a crucial role in measuring the degree of dissimilarity among data points. When creating and optimizing machine learning models, data scientists and machine learning practitioners can make more informed choices by understanding the features of popular distance metrics and their relationships. The effectiveness and interpretability of the model's output can be greatly influenced by selecting the appropriate distance metric. We explain distance metrics and their relevance in machine learning with various examples of metrics, including Minkowski distance, Manhattan distance, Max Metric for R^n, Taxicab distance, Relative distance, and Hamming distance.